IDENTITY IN CONSUMPTION: EXPLORING FOOD AND INTERSECTIONALITY IN ANITA DESAI’S FASTING, FEASTING (International Journal of Food and Nutritional Sciences, 2022)
Food Studies is on a sudden rise with wide explorations to add contextual meaning to surface and deep meanings. The resurgence of Food Studies has given rise to multifaceted analyses across various disciplines, particularly in literary contexts where food often serves as a symbolic element rather than merely sustenance. This paper delves into Anita Desai’s novel Fasting, Feasting (1999), using the lens of food and foodways to explore the interactions of characters within the culinary sphere and their broader implications on identity. The study emphasizes how these interactions reveal intersectional gender identities influenced by nationality, class, and other social factors. Additionally, it investigates the theme of marginalization, particularly focusing on gender as a decisive element. The title of the novel itself—suggests consumption in both its presence and absence and provides a framework for examining which characters enjoy abundance and who are left wanting.